Complete Genome Sequence of Undomesticated Bacillus subtilis Strain NCIB 3610 - Nye, Taylor M. (Genome Announc, 2017)
Bacillus subtilis is a Gram-positive bacterium that serves as an important experimental system. B. subtilis NCIB 3610 is an undomesticated strain that exhibits phenotypes lost from the more common domesticated laboratory strains. Here, we announce the complete genome sequence of DK1042, a genetically competent derivative of NCIB 3610.